How can we improve the stability of organic solar cells from materials design to device engineering? - Mingpeng Li; Leilei Tian; Feng He (Aggregate)
Abstract Among a promising photovoltaic technology for solar energy conversion, organic solar cells (OSCs) have been paid much attention, of which the power conversion efficiencies (PCEs) have rapidly surpassed over 20%, approaching the threshold for potential applications. However, the device stability of OSCs including storage stability, photostability and thermal stability, remains to be an enormous challenge when faced with practical applications. The major causes of device instability are rooted in the poor inherent properties of light‐harvesting materials, metastable morphology, interfacial reactions and highly sensitive to external stresses. To get rid of these flaws, a comprehensive review is provided about recent strategies and methods for improving the device stability from active layers, interfacial layers, device engineering and encapsulation techniques for high‐performance OSC devices. In the end, prospectives for the next stage development of high‐performance devices with satisfactory long‐term stability are afforded for the solar community.